Implementation of Character Education for Elementary School Children in the Digital Age - Setiyorini, Dwi; Jayanti, Ratmi (Sekolah Tinggi Ilmu Tarbiyah Bustanul 'Ulum Lampung Tengah, 2025)
Implementing Character Education for Elementary School Children in the Digital Era at MI Unggulan Miftahul Huda Wanengpaten Gampengrejo Kediri presents a crucial challenge of harmonizing traditional values with contemporary digital influences. In response to the pressing need to cultivate moral and ethical fortitude in students amidst ubiquitous digital exposure, this qualitative study aims to investigate effective strategies for character education implementation. Through methods including observations, interviews, and document analysis, insights were gathered into the multifaceted approach required to instill virtues such as responsibility, respect, and resilience. The findings underscored the significance of integrating character education across the curriculum and leveraging digital platforms constructively to reinforce positive behaviors and values. Teachers emerged as pivotal figures in modeling and guiding students towards ethical decision-making in both offline and online contexts. Collaborative efforts involving educators, parents, and the community were identified as critical for creating a supportive ecosystem that nurtures character development. The implications of this study emphasize the importance of proactive measures to equip elementary school children with the moral compass and skills necessary to navigate the digital landscape responsibly. By fostering a culture of integrity and ethical awareness early on, schools can prepare students to contribute positively to society while safeguarding their well-being in an increasingly digitalized world. This research contributes valuable insights into enhancing character education practices tailored to the challenges and opportunities of the digital era.